2019
DOI: 10.1177/0954405419845572
|View full text |Cite
|
Sign up to set email alerts
|

Comparison among the environmental impact of solid state and fusion welding processes in joining an aluminium alloy

Abstract: The life-cycle assessment methodology was used to evaluate the environmental impact of friction stir welding of AA5754-H114 aluminium alloy sheets. Other works in literature considered the environmental impact of friction stir welding, but in this study the influence of different process parameters on midpoint category impacts were analysed. Friction stir welding was performed under different values of rotational and welding speeds. Moreover, pin tool wear and mechanical properties of joints were also evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Although (with the exception of the YS changes for transversal orientation (Figure 13b)) the variations presented in Figure 13 are very moderate, these trends are, in qualitative terms, opposite to those described in the literature [15,16,27]. In general, with increasing traverse speed, the amount of thermal energy generated during FSW decreases [4]. This contributes to maintaining higher strength parameters due to the lower intensity of the copper recrystallisation process.…”
Section: Monotonic Tests Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Although (with the exception of the YS changes for transversal orientation (Figure 13b)) the variations presented in Figure 13 are very moderate, these trends are, in qualitative terms, opposite to those described in the literature [15,16,27]. In general, with increasing traverse speed, the amount of thermal energy generated during FSW decreases [4]. This contributes to maintaining higher strength parameters due to the lower intensity of the copper recrystallisation process.…”
Section: Monotonic Tests Resultsmentioning
confidence: 62%
“…In particular, this technique can be used as one of few methods for joining metals that are hard to weld or have physicochemical properties significantly different from each other, i.e., in cases when the use of conventional fusion welding is strongly limited and braze welding does not yield sufficient joint strength [2]. For this reason, FSW is commonly used not only for welding aluminium alloys [3,4] but also for many other metallic materials such as magnesium alloys [1,[5][6][7], titanium alloys [1,8], steel [9,10], copper [11][12][13][14][15][16], and different combinations of dissimilar metals [1].…”
Section: Introductionmentioning
confidence: 99%
“…According to [7], the friction stir welding process is mostly used to join "unweldable" materials, such as aluminum alloys, since they do not reach melting temperature and solidify during the welding process. Moreover, FSW is receiving increasing interest owing to the energy efficiency, environment friendliness and versatility that make the process a promisingly ecologic and "green" technology [22,25]. Furthermore, the mechanical properties and post-welding formability of joints in aluminum alloys manufactured by FSW are known to be slightly higher respect to laser welding.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, it was demonstrated that, among process parameters, the rotational speed and welding speed have a strong effect on heat generation, heat dissipation and cooling rate. Thence, joint formation, microstructure of joints and forces developed during FSW process are significantly influenced by ω and v values [1,3,7,15,17,[20][21][22][23][24][25][26][27][28][29][30].…”
Section: Fsw Process Peculiaritiesmentioning
confidence: 99%
“…The most attractive reason for joining aluminum alloys through FSW is the avoidance of typical defects, such as porosities, inclusions, distortions, residual stresses and cracks, developed during conventional fusion welding processes [9]. In addition, as shown by Bevilacqua et al on AA5754 aluminum alloy, FSW is an environmentally friendly process as compared with conventional techniques such as gas tungsten arc welding and laser beam welding [10,11]. Many studies have proven that FSW is suitable in the manufacturing of tailored welded blanks with different materials and/or thicknesses.…”
Section: Introductionmentioning
confidence: 99%